182: Evaluation of a Clinical Score for Skull Radiography of Young Children with Isolated Head Trauma. Issue 6 (1st June 2014) - Gravel, J; Gouin, S; Chalut, D; Crevier, L; Masse, B
Abstract: BACKGROUND: A clinical score was reported in 2010 by Bin et al to identify head-injured infants that are at higher risk of skull fracture. OBJECTIVES: To determine the criterion validity of the clinical score to identify skull fracture among children younger than two years old with head trauma and no need for head tomography. DESIGN/METHODS: A prospective cohort study was conducted in two pediatric emergency departments. Participants were all children younger than 24 months who sustained a head trauma and for whom head tomography was not highly recommended according to the PECARN head CT scan rule. The exposure of interest was the clinical score (from 0 to 8) composed of the age of the patient, the size and location of the hematoma. The previous study suggested that a score higher than two would be predictive of skull fracture. The primary outcome was the presence of a skull fracture according to radiological report. All participants were initially evaluated by a physician using a standardized datasheet before radiological evaluation. Skull radiography ordering was left at the primary physician's discretion. The primary analysis was the association between the clinical score and presence of a skull fracture. It was estimated that a sample of 50 cases of fracture would provide a width of ±0.05 if the sensitivity of the score was higher than 0.90. RESULTS: A total of 765 patients were recruited during the study period. Among them, 271 had a radiological evaluation and 50 had a skull fracture. Most children had low clinical score but 209 had a score >2. A clinical score >2 points resulted in a sensitivity of 0.86 (95% CI 0.74 to 0.93) and a specificity 0.77 (95% CI 0.74 to 0.80). CONCLUSIONS: The clinical decision score demonstrated a moderated sensitivity to identify children at risk of skull fracture. Further studies are required to derive a useful clinical decision rule for young children with head trauma.